Digital design : a critical introduction - Bruton, Dean.; Radford, Anthony; Radford, Antony (London ; New York : Berg, 2012)
"Digital media are revolutionising design, both as a tool in design practice and as a way of thinking about design products, processes and systems. Digital Design outlines the rules and patterns that underlie digital media and clearly explains how they improve design outcomes. But Digital Design is about breaking and bending the rules as well as following them. The book reveals how a combination of systematic thinking (understanding and using rules and patterns) and intuitive thinking (adapting and inventing for specific situations) can enhance the work of a digital designer. Written for both experienced and novice designers, Digital Design is superbly illustrated with over 200 black and white and colour images. With its unique combination of analysis and how-to, the book is inspiring for students of visual effects, animation, game, website and architectural design, and product and graphic design in a broader sense"--
"Digital Design: A Critical Introduction provides a much-needed new perspective on designing with digital media. Linking ideas from media theory, generative design and creativity with examples from nature, art, architecture, industrial design, websites, animation and games, it addresses some fundamental questions about creative design with digital media. Featuring original material based on the authors' own research, the book argues that the recognition and understanding of the interplay of the two apparently opposing concepts of rules and contingency supports original thinking, creativity and innovation. Going beyond existing texts on the subject, Digital Design is an accessible primer whose innovative approach transcends the analysis of individual subfields - such as animation, games and website design - yet offers practical help within all of them"--
Keywords: Computer-aided design; COMPUTERS / CAD-CAM.; DESIGN / Product; ARCHITECTURE / Design, Drafting, Drawing & Presentation